2019
DOI: 10.1002/admi.201900300
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Assisted Liftoff of Polycrystalline CdS/CdTe Thin Films Using Heterogeneous Interfacial Engineering

Abstract: Recent advances in device design and process optimizations have enabled the production of CdTe devices on flexible substrates, but the necessary high-temperature processing (> 450 °C) to recrystallize grains limits the use of alternative lightweight substrates. Here, we report a new synthesis method to create a freestanding CdS/CdTe film by combining hightemperature depositions (CdS/CdTe on Si/SiO 2 ) and a simple lift-off process in a water environment at room temperature. Analysis of the results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In this case, the goal was to fabricate lightweight, flexible devices so a polyimide carrier layer was inserted between the NaCl and device stack which still left the buried interfaces inaccessible. Polycrystalline CdS/CdTe films have also been delaminated from Si wafers using a water‐assisted method, [ 45 ] in which case the interface could be studied. However, it is likely that the interface was altered during this process, e.g., through removal of the water‐soluble CdCl 2 layer that was likely accumulated there [ 20 ] and has been shown to passivate that interface.…”
Section: Achieving Successful Delaminationmentioning
confidence: 99%
“…In this case, the goal was to fabricate lightweight, flexible devices so a polyimide carrier layer was inserted between the NaCl and device stack which still left the buried interfaces inaccessible. Polycrystalline CdS/CdTe films have also been delaminated from Si wafers using a water‐assisted method, [ 45 ] in which case the interface could be studied. However, it is likely that the interface was altered during this process, e.g., through removal of the water‐soluble CdCl 2 layer that was likely accumulated there [ 20 ] and has been shown to passivate that interface.…”
Section: Achieving Successful Delaminationmentioning
confidence: 99%
“…81 Recently, Magginetti et al reported that CdS/CdTe thin films can also be readily lifted-off from SiO 2 /Si substrates via waterassisted thin film delamination method due to the Te-rich layer at SiO 2 surface. 82 This approach makes it possible to use the conventional fabrication process such as high temperature annealing, which is otherwise not possible on flexible substrates such as plastic foil, by utilizing metal/SiO 2 /Si substrate system. It also allows the transfer of fully fabricated device layers without needing any hazardous chemical etchants.…”
Section: Crack-assisted Layer Transfer With Interfacial Fracture Toug...mentioning
confidence: 99%
“…Similarly, a graphene monolayer can be separated from the copper foil used as the growth substrate by a roll-to-roll mechanical delamination process in hot water (∼50 °C) . Recently, Magginetti et al reported that CdS/CdTe thin films can also be readily lifted-off from SiO 2 /Si substrates via water-assisted thin film delamination method due to the Te-rich layer at SiO 2 surface . This approach makes it possible to use the conventional fabrication process such as high temperature annealing, which is otherwise not possible on flexible substrates such as plastic foil, by utilizing metal/SiO 2 /Si substrate system.…”
Section: Crack-assisted Layer Transfer With Interfacial Fracture Toug...mentioning
confidence: 99%
“…Lift-off is an attractive approach to fabricate flexible CdTe solar cells due to its low-cost fabrication process. Currently, a variety of lift-off methods have been developed to fabricate flexible CdTe solar cells, including scarification layer-assisted lift-off, ,, mechanical lift-off, , thermomechanical stress, and water-assisted lift-off. Water-assisted lift-off to fabricate flexible CdTe solar cells is a technique that was recently reported by Wen and co-workers through lifting epitaxial CdTe films off from a muscovite mica (K 2 O·Al 2 O 3 ·SiO 2 ) substrate. This approach exhibits advantages including less stress in CdTe films and ambient operation temperature.…”
Section: Introductionmentioning
confidence: 99%